2024
DOI: 10.1109/tem.2022.3157625
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of IoT on the Performance of Vaccine Supply Chain Distribution in the COVID-19 Context

Abstract: The Government of India has started the distribution of the Covishield and Covaxin vaccines across all the comprising states. In developing states like Bihar, the vaccine supply chain (VSC) is likely to face many challenges due to poor health infrastructure, multidimensional poverty, and poor literacy. Supply chain practitioners are experimenting with available technologies to deal with supply, demand, and behavioral challenges. The present research work seeks to inspect the potential impact of Internet of Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…A study shows that diverse teams and leadership are more likely to develop environmental strategies that contribute to sustainable mechanisms (Figueroa-Domecq et al, 2020). This study also found that women were more likely to focus on environmental sustainability when leading tourism enterprises (Anser et al, 2020b;Latif et al, 2020;Kumar et al, 2022;Yang et al, 2022;Zaman et al, 2022). However, men had shown their interest in being part of economic sustainability (Pitafi et al, 2018(Pitafi et al, , 2019(Pitafi et al, , 2020Anser et al, 2020b;Latif et al, 2020;Rashid et al, 2020).…”
Section: Environmental Sustainabilitymentioning
confidence: 75%
“…A study shows that diverse teams and leadership are more likely to develop environmental strategies that contribute to sustainable mechanisms (Figueroa-Domecq et al, 2020). This study also found that women were more likely to focus on environmental sustainability when leading tourism enterprises (Anser et al, 2020b;Latif et al, 2020;Kumar et al, 2022;Yang et al, 2022;Zaman et al, 2022). However, men had shown their interest in being part of economic sustainability (Pitafi et al, 2018(Pitafi et al, , 2019(Pitafi et al, , 2020Anser et al, 2020b;Latif et al, 2020;Rashid et al, 2020).…”
Section: Environmental Sustainabilitymentioning
confidence: 75%
“…Vaccines are central to any immunization program, and coordinating its flow from manufacturing centers to the beneficiaries is achieved worldwide through a complex supply chain that includes cold storage and transportation (Li et al, 2022). Managing vaccine demand, distribution, wastage and stock information is crucial to the internal process performance of any vaccine supply chain (VSC) (Chandra and Kumar, 2021;Kumar et al, 2022;Li et al, 2022). However, several underdeveloped and developing countries cannot attain the standards set by WHO and UNICEF for storing, handling, distribution, and stock management of vaccines (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Finkenstadt and Handfield, 2021). Integrating modern technology infrastructure and training the concerned officials for effective adaptation, internal assessment and service innovation can resolve these issues (Gurnani et al, 2020;Kumar et al, 2022;Yan, 2017). It is vital to assess the impact of these technological interventions using relevant VSC performance indicators (PIs) to justify the efforts and investments made while implementing them and simultaneously identify the PIs which show relatively minor improvement for a given region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations